A diffusion index analysis of the Argentinean business economic cycle during the COVID-19 pandemic - Pedro Elosegui; Mirta González; María Cecilia Pérez; Máximo Sangiácomo (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2022)
The Central Banks use diffusion indexes (DIs) to synthesize information from proprietary surveys that complement official statistics generating real time proxies of the economically relevant variables. According to the evidence, the DIs closely follow the economic cycle reflected in those official statistics. In this paper, the Survey of Business Economic Perspectives collected by the Central Bank of Argentina, is used to calculate two diffusion indexes: (i) the marginal diffusion index (MDI) based on the balance of answers and demeaned by the averaged participant response aiming at correcting for the "respondent bias" and; a (ii) marginal fixed diffusion index (MFDI) that corrects the ex-post changes on past MDI index generated by changes in the average participant response. Both indexes are analyzed for the 2017-2022 period, a particularly volatile business cycle for Argentina and (given the impact of Covid-19) for the global economy. An econometric procedure aimed at assessing the indexes relationships with the official economic activity indicators is introduced. The analysis indicates that the DIs calculated with the BCRA's Survey information closely follow and even anticipate the behavior of other official activity indicators both for the entire sample of firms and the industrial sector.
Keywords: C18; C83; E32; E66; 330; Diffusion Index; Business cycle; Economic Activity